2016
DOI: 10.17222/mit.2014.293
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Taguchi method to select the optimum cutting parameters for tangential cylindrical grinding of AISI D3 tool steel

Abstract: The purpose of this research was an analysis of the optimum cutting conditions for the lowest surface roughness in tangential cylindrical grinding of the AISI D3 tool steel using the Taguchi method. In this experimental investigation, the surface roughness with various wheel speeds, workpiece speeds, feed rates and depths was observed. The surface roughness was investigated employing the Taguchi design of experiments and an analysis of variance (ANOVA). Significant machining parameters were identified using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Applying formulas ( 5), (6) to calculate ni value. Applying formulas (7), (8) to calculate vi value. The results are presented in Table 4.…”
Section: Multi-criteria Decision Making Using the Waspas Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying formulas ( 5), (6) to calculate ni value. Applying formulas (7), (8) to calculate vi value. The results are presented in Table 4.…”
Section: Multi-criteria Decision Making Using the Waspas Methodsmentioning
confidence: 99%
“…Study on determination of cutting parameters to ensure the minimum value of surface roughness when grinding the AISI D3 steel was also performed according to matrix using Taguchi method. S/N method was also applied to analyze the experimental results [8]. The analyzed results showed that to obtain the smallest surface roughness, the grinding wheel speed was 2000 rev/min, workpiece speed 220 rev/min, feed rate was 3.2 mm/rev, and depth of cut was 0.005 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The work on cylindrical grinding had also been reported by various researchers (Kumar et al 2016, Ozay et al 2016. The grinding wheel grain size and work speed are the most influential parameters that affect MRR and R a (Kumar et al 2016).…”
Section: Introductionmentioning
confidence: 87%
“…The grinding wheel grain size and work speed are the most influential parameters that affect MRR and R a (Kumar et al 2016). The parameters like depth of cut and feed rate increases the surface roughness, while the wheel speed reduces the roughness in the cylindrical grinding of AISI D3 tool steel (Ozay et al 2016). Demir et al (2010) reported that an increase in grain size and depth of cut influenced the grinding forces and surface roughness of the ground samples.…”
Section: Introductionmentioning
confidence: 99%
“…During the machining process of Inconel 718 (Kivak, 2012), tool temperature easily increases due to the low thermal conductivity of this material. As a result of the higher toughness level of the material, shavings formation proves challenging during the machining process (Ay, 2010;Özay et al, 2016;Savaş et al, 2016). As the manufacturing cost of this material is relatively high, any fault during the machining process may lead to serious monetary losses (Ay et al, 2010;Lima et al, 2016;Bhattacharya et al, 1983;Özay et al, 2016;Savaş et al, 2016).…”
Section: Introductionmentioning
confidence: 99%